Analysis of the Potentiometric Titration Curves of Weakly Basic Anionites - A.V. Mamchenko; L.G. Chernova (Adsorption Science & Technology)
An analysis of the experimental potentiometric titration curves for various classes of weakly basic anionites has been made from the basis of the exchange equilibrium theory. When the NaCl concentration in the external solution differed by more than two orders of magnitude, two curves were obtained for each ionite. Reference to the activities of the chloride ions allowed these two curves to be combined satisfactorily. The acrylic anionite, Amberlite IRA 67, fulfilled the model of ideal exchange in the gel phase. Systematic deviations from such ideal behaviour were observed for the polystyrene–divinylbenzene anionite, Lewatit MP 62, while the experimental data for Lewatit AP 49 exhibited an essential deviation from a linear dependence when plotted in terms of the extended Henderson–Hasselbalch equation. Comparative analyses of the titration curves for weakly basic Amberlite IRA 67, strongly basic AB 17-8 and Lewatit AP 49 anion exchangers led to the suggestion that Lewatit AP 49 contained weak and strong basic groups whose behaviour may be described by the extended Henderson–Hasselbalch equation using various effective equilibrium constants but the same value of n (= 1). An equation for calculating the quantity of strong and weak basic groups in an acrylic anionite has been obtained. An explanation of ideality in terms of weakly dissociating (basic) and strongly dissociating (salt) resinates of weakly basic acrylic anion-exchange resins has been proposed.